If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -67(-1) = y Multiply -67 * -1 67 = y Solving 67 = y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 67 + -1y = y + -1y Combine like terms: y + -1y = 0 67 + -1y = 0 Add '-67' to each side of the equation. 67 + -67 + -1y = 0 + -67 Combine like terms: 67 + -67 = 0 0 + -1y = 0 + -67 -1y = 0 + -67 Combine like terms: 0 + -67 = -67 -1y = -67 Divide each side by '-1'. y = 67 Simplifying y = 67
| 93=-54+c | | 16000/160= | | 18=8*6+b | | 3+(-78)=x | | 1=x-47/4 | | 233-(-3)=y | | 10-v+5+6v=1+5v+3 | | -12=-69+r | | 11=y-(-3) | | 5=y-(-1) | | p=8*18+23 | | 64+t=-65 | | 96m-8=2+9m | | 12=r-65 | | p=3*18+27 | | s+95=-35 | | 4n+6-2n=(n-13) | | u-20=20 | | 71=63+b | | -17=x+69 | | 89=-64+w | | y-(-3)=9 | | 15=-18+a | | 25=8*6+b | | 12=3-(-1y) | | c+31=-3 | | a-22=-1 | | p=18(-64) | | 2+3(x+6)=11-(5x+15) | | 1.8r+9=-5 | | s-44=-36 | | 4b^2w^3/3c^2k+5x^2/6b^3k^2 |